Direct Modeling of Chemical Processes in Conditions of Uncertainty of Initial Data - A. Medvedeva, Olga; I. Mustafina, Sofya; V. Grigoryev, Igor; A. Mustafina, Svetlana (International Journal of Engineering and Technology, 2018)
The paper studies the influence of uncertainty in kinetic parameters on the results of solving the direct problem of chemical kinetics. The direct problem of chemical kinetics is a calculation of multicomponent reacting-mix composition and speed of reaction on the basis of the set mathematical model with known parameters. Kinetic data are represented in intervals and are considered as objects of interval analysis. The computational experiment was carried out for the reactions proceeding without the change of reaction volume (reaction of reception of phthalic anhydride) and taking into account its change (reaction of oligomerization of Î±-methylstyrene). On the basis of methods of interval analysis the boundaries of solution of the direct problem of chemical kinetics caused by interval representation of kinetic parameters are obtained. In the example of reaction of oligomerization of Î±-methylstyrene, during which there is a change of the number of moles of a reaction mixture, and reaction of reception of phthalic dioxide flowing with constant reaction volume, various ways of construction are considered in interval expansion of the right parts of the differential equations that determine the type of kinetic model of the reactions studied.Â Â